2005
DOI: 10.1097/01.csmr.0000306221.25551.69
|View full text |Cite
|
Sign up to set email alerts
|

Neck and Back Pain in Bicycling

Abstract: Neck and back pain are among the most common overuse injuries in cyclists. Bicycle fit, improper equipment, training errors, and individual anatomic factors are important evaluation considerations. By learning how to recognize and treat contributing factors, as well as learning a few simple bike-fitting techniques, physicians can treat and prevent many common problems of this popular activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
11
0
6

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 7 publications
1
11
0
6
Order By: Relevance
“…However, knee joint, cervical and lumbar regions of the spine are the most common localizations of overuse injuries [7,18].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, knee joint, cervical and lumbar regions of the spine are the most common localizations of overuse injuries [7,18].…”
Section: Discussionmentioning
confidence: 99%
“…Muyor et al [21] reported spinal adaptive changes in cyclists: thoracic hyperkyphosis in standing (smaller in sitting) and higher anterior pelvic tilt. Long-lasting inclination occurring during cycling can contribute to pain in the cervical curve (hyperlordosis in watching the terrain) [18]. Srinivasan et al [22] showed a significant difference in spinal muscle fatigue in people depending on whether or not they experienced pain.…”
Section: Discussionmentioning
confidence: 99%
“…A alteração da inclinação do selim como conduta para resolver a lombalgia é questionada por Goméz-Puerto et al (2008) e pode, ainda, desencadear dor nas mãos (KRONISCH, 1998a;SILBERMAN et al, 2005) por aumentar a pressão na região tenar e hipotenar. Por outro lado, um guidão relativamente baixo pode estar relacionado a um reduzido ângulo da mesa (PRUITT; MATHENY, 2006) e ainda ser o responsável por acentuar a flexão de tronco, aumentando a tensão nas estruturas musculoesqueléticas da região lombar (ASPLUND; WEBB; BARKDULL, 2005). Garantir a adequada altura do guidão, do comprimento do tubo superior efetivo e flexão de tronco do ciclista ajuda a minimizar ou até mesmo eliminar a lombalgia (MELLION, 1994;WEBB;BARKDULL, 2005).…”
Section: Discussionunclassified
“…Como a postura de flexão de tronco é mantida por longos períodos durante a prática ciclística, a tendência é que os músculos que realizam a estabilização e extensão da coluna vertebral entrem em fadiga, diminuindo a resistência do atleta para a manutenção da postura (USABIAGA et al, 1997). Desta forma, o fortalecimento da musculatura lombo-pélvica e o alongamento de músculos dos membros inferiores ajuda a prevenir a ocorrência de disfunções lombares e aumenta o desempenho na prática esportiva (MELLION, 1994;WEBB;BARKDULL, 2005).…”
Section: Discussionunclassified
See 1 more Smart Citation